Coupled chemo(enzymatic) reactions in continuous flow - Yuryev, Ruslan; Strompen, Simon; Liese, Andreas (Beilstein Journal of Organic Chemistry, 2011)
This review highlights the state of the art in the field of coupled chemo(enzymatic) reactions in continuous flow. Three different approaches to such reaction systems are presented herein and discussed in view of their advantages and disadvantages as well as trends for their future development.
Keywords: biocatalysis; chemo-enzymatic reaction sequences; continuous flow; coupled reactions; reaction cascades